(untitled) (Research, Society and Development, 2020)
Introduction: In restorative dentistry, the faceting of teeth with aesthetic compromise is considered an effective procedure in which the clinician must choose the ideal treatment and select appropriate materials to obtain satisfactory and predictable aesthetic results. In this sense, the use of the Advanced Polymerization System (APS) has advantages, such as aesthetics, durability, degree of conversion and minimal color change. Objective: Demonstrate the aesthetic-functional restoration using adhesive system and composite resin with APS polymerization technology. Case report: A female patient attended the Integrated Clinic of the Faculty of Dentistry of UFRJ with a complaint of blackening of teeth related to ceramic laminates. After clinical and radiographic examination, it was decided to use composite resin veneers. Results: The composite resin veneers associated with the adhesive system promoted an excellent aesthetic result. Conclusion: The improvement of direct restorations with acid etching techniques and the use of new adhesive systems, combined with the constant development and scientific improvement of composite resins, enabled dentists to perform restorations in the most diverse clinical indications.